Arctic migrating barnacle geese utilize accommodation fields in a new agricultural staging area - Seltmann, Martin W.; Ylitalo, Anna‐Kaisa; Piironen, Antti; Store, Ron; Heikkinen, Juha; Heim, Wieland; Piha, Markus; Seimola, Tuomas; Laaksonen, Toni; Forsman, Jukka T. (Wiley-Blackwell, 2025)
The recovery of threatened species after conservation measures can lead to human–wildlife conflicts. One example of such is the recent population growth of the Barnacle Goose Branta leucopsis, a large herbivorous bird. During migration, geese stage in large numbers on agricultural fields in range countries and cause substantial damage to farms. A combination of repelling fields, where geese were chased off by humans, and accommodation fields, which provide refuge sites for foraging geese, has been suggested as an effective management tool to mitigate conflicts.Using high-resolution satellite tracking data, we investigated habitat selection of 41 barnacle geese staging in Northern Karelia, Finland, during spring 2021. We estimated relative habitat use by these geese and conducted a fine-scale analysis of their use of different fields by employing Hidden Markov Models and integrated step-selection analysis. Fields included normal crop (no goose management), project and other (private and Nature 2000 area) accommodation fields and repelling fields. Project accommodation and repelling fields were established on areas known to have a long history of high grazing pressure by barnacle geese.We found that behavioural data of geese can be categorized into three different states (static, slow and fast movement). Static and slow states were used for local field selection, fast state for field selection in the regional area, and all states for field selection after leaving a repelling field.Overall, relative habitat use indicated that geese utilize accommodation fields more than expected by their availability. Integrated step-selection analyses revealed that geese avoided normal and repelling versus project accommodation fields at the regional scale. At the local scale, they preferred project accommodation fields over all other fields. After leaving a repelling field, geese did not show preference for any accommodation over repelling fields.Synthesis and application. Geese show individual selection for accommodation fields compared to normal or repelling fields across several scales. Our results suggest that the accommodation field concept—consisting of refuge areas and no-go areas where geese are repelled from—can help to mitigate the human–wildlife conflict using local stakeholders' knowledge.
Keywords: Branta leucopsis; habitat selection; hidden Markov model; human–wildlife conflict; integratedstep-selection analysis; Karelia (Finland); population management; tracking (telemetry)